2004
DOI: 10.1197/j.aem.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Silver Sulfadiazine, Biafine, and Saline‐soaked Gauze in the Treatment of Superficial Partial‐thickness Burn Wounds in Pigs

Abstract: Silver sulfadiazine 1% cream (SSD) and biafine (an oil-inwater emulsion containing alginate) are used for the treatment of superficial partial-thickness burns, but comparative effectiveness studies are lacking. Objectives: To compare the uses of SSD, Biafine (Labortoires Medix, Houdan, France), and saline-soaked gauze in the treatment of superficial partial-thickness burns in pigs. Methods: This was a randomized controlled trial in four anesthetized young pigs. Four equal sets of partial-thickness contact burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Although promising, this technique so far has not been used for the evaluation of the course of wound healing in randomized clinical trials. Still the most common way to determine the healing of burn injuries is based on clinical parameters such as rate of reepithelialization, pain level, healing time, scar formation, and patient satisfaction 3–5 . This said, the need for an objective in vivo tool to assess the histomorphological features of wound healing becomes evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although promising, this technique so far has not been used for the evaluation of the course of wound healing in randomized clinical trials. Still the most common way to determine the healing of burn injuries is based on clinical parameters such as rate of reepithelialization, pain level, healing time, scar formation, and patient satisfaction 3–5 . This said, the need for an objective in vivo tool to assess the histomorphological features of wound healing becomes evident.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced knowledge of burn wound pathophysiology can improve treatment outcomes by reducing patient morbidity and mortality, rate of scar formation, and potentially reduce the healing times as well as the overall costs of burn‐specific wound management. Numerous studies have focused on the pathophysiology of burn wound healing 1–5 . However, the currently utilized observational methods assess the burn wound‐healing course mainly via evaluation of the microcirculation 6 .…”
mentioning
confidence: 99%
“…15,16 A study evaluating healing times in partial thickness burn wounds in pigs found no difference between SSD, Biafi ne and salinesoaked gauze. 17 Although the pathophysiology of chemical, thermal and ultraviolet radiation induced burns is distinct from that of acute radiation dermatitis, there is a risk of bacterial infection in all cases because of compromised skin barrier function. 18 All facilities in this survey using 2% chlorhexidine gluconate soaks or sprays combined this treatment with topical SSD.…”
Section: Topical Therapymentioning
confidence: 99%
“…However, excisional wounds lack the avascular eschar of burn wounds that provides a microenvironment conducive for bacterial growth and colonization . Others have used uninoculated porcine burn models to test antimicrobial burn dressings, in particular for their ability to improve burn wound healing . We demonstrate here that uninoculated burn wounds contain relatively low levels (<10 4 cfu/g) of P. aeruginosa and S. aureus , two bacteria commonly associated with infected burn wounds .…”
Section: Discussionmentioning
confidence: 64%
“…To allow for the direct comparison of sustained antimicrobial activity between silver sulfadiazine and ciprofloxacin‐loaded keratin hydrogels, reapplication of all treatments occurred once every 3–4 days for the first 15 days postinjury. Therefore, it was no surprise that silver sulfadiazine did not reduce bacteria levels, or affect healing (data not shown), as we did not follow the manufacturer's recommended usage for twice‐daily application …”
Section: Discussionmentioning
confidence: 99%